Developing resources to facilitate public conversations about the use of linked address-based data for research - Firman, Nicola; Dezateux, Carol; Newman, Claire; Baird, Harriet; Fry, Rich; Harper, Gill; Griffiths, Lucy; Dibben, Chris; Robert, Alison; Thomson, Alison (International Journal of Population Data Science, 2026)
Introduction Unique Property Reference Numbers (UPRNs) provide every addressable location in the United Kingdom (UK) with an identifier up to 12-digits in length, which are persistently unique, and are a mandated standard across the public sector in the UK. This standardisation means they are suited to be pseudonymised for data linkage for research, innovation and public benefit. While there have been many consultations exploring public trust in, and attitudes to, using patient data for research, none have explicitly considered their use for address-based linkage using UPRNs. Objectives Our overarching aim is to build public trust in the uses of address-based data at household level. We set out to develop and test materials to facilitate conversations about the use of address-based data linkage at the household-level. In this case study, we describe the development of information materials and an initial dialogue to inform future public deliberation. Methods In collaboration with designers and researchers, we generated a prototype website and shared this with experienced public advisory groups. Feedback from these groups informed development of a suite of resources, including slides and a facilitator's script to guide workshop discussions. These were supplemented by interactive, tactile tools designed to promote understanding of key concepts, and to encourage participants to ask questions relevant to their interests and concerns. We hosted two workshops with residents in a multi-ethnic, disadvantaged inner city locality to test and refine these materials. Results Dialogue with residents emphasised the importance of accessibility, including clear descriptions of technical jargon, and the effectiveness of using less text-heavy materials and more interactive formats, particularly for participants for whom English is not their first language. Visual representations of people included in workshop materials need to reflect diversity in age, gender, ethnicity, and mobility to ensure resources are relatable. Adapting the approach to delivering information - whether through digital or physical formats - proved crucial in engaging with participants and meeting their diverse needs. Conclusions We have created and tested with different public groups a toolkit to support conversations with academic and public audiences about research using address-linked patient data. The toolkit has been disseminated and made freely available for use by the research community.